Markerless analysis of front crawl swimming - Ceseracciu, E.; Sawacha, Z.; Fantozzi, S.; Cortesi, M.; Gatta, G.; Corazza, S.; Cobelli, C. (Journal of Biomechanics, 2011)
Research on motion analysis of swimmers is commonly based on video recordings of the subject's motion, which are analyzed by manual digitization of feature points by an operator.